Stroke hospitalizations, posttraumatic stress disorder, and 9/11‐related dust exposure: Results from the World Trade Center Health Registry. Issue 10 (19th July 2021) - Yu, Shengchao; Alper, Howard E.; Nguyen, Angela‐Maithy; Maqsood, Junaid; Brackbill, Robert M.
Abstract: Background: Few studies have examined the association between disaster‐related factors and stroke by subtype or number. We investigated the association between 9/11‐related posttraumatic stress disorder (PTSD), dust exposure, and stroke subtype as well as recurrent strokes. Methods: The study included 29, 012 individuals enrolled in the World Trade Center Health Registry. Stroke cases were obtained by matching Registry enrollees to the New York State Department of Health's discharge records for inpatient visits between 2000 and 2016. Cox proportional hazards regression models were performed to examine the association between 9/11‐related risk factors and stroke by subtype. Multinomial logistic regression models were conducted to assess the associations between the same risk factors and the number of stroke hospitalizations. Results: Having PTSD significantly increased the risk of developing ischemic and hemorrhagic stroke, with adjusted hazards ratios (AHRs) of 1.64 (95% confidence interval [CI]: 1.28–2.10) and 1.73 (95% CI: 1.10–2.71), respectively. The point estimate for dust cloud exposure, although not significant statistically, suggested an increased risk of ischemic stroke (AHR = 1.20, 95% CI: 0.96–1.50). PTSD was significantly associated with recurrent strokes with an adjusted odds ratio of 1.79 (95% CI: 1.09–2.95). Conclusions: PTSD is a risk factor for both ischemic and hemorrhagic stroke and is associated with recurrent strokes. Dust exposure on 9/11 is a possible risk factor for ischemic stroke but not for hemorrhagic stroke, and was not associated with recurrent strokes. Our findings warrant additional research on stroke‐morbidity and mortality associated with 9/11‐related PTSD and dust exposure.